2013
DOI: 10.1371/journal.pone.0052706
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Agent Shikonin Is an Incompetent Inducer of Cancer Drug Resistance

Abstract: PurposeCancer drug resistance is a major obstacle for the success of chemotherapy. Since most clinical anticancer drugs could induce drug resistance, it is desired to develop candidate drugs that are highly efficacious but incompetent to induce drug resistance. Numerous previous studies have proven that shikonin and its analogs not only are highly tumoricidal but also can bypass drug-transporter and apoptotic defect mediated drug resistance. The purpose of this study is to investigate if or not shikonin is a w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 49 publications
1
49
0
2
Order By: Relevance
“…The IC 50 value was 12.75 ± 0.84 mol·L -1 after 72 h treatment, 24.82 ± 0.94 mol·L -1 after 48 h, and 61.41 ± 1.08 mol·L -1 after 24 h. In the present investigation, geraniin revealed growth inhibitory activity against A549 cells, which was superior to shikonin after treatments of 72 and 48 h and showed a similar result to shikonin after 24 h (Fig. 1) (Wu et al 2013). …”
Section: Cytotoxicity Of Geraniin In Vitrosupporting
confidence: 65%
“…The IC 50 value was 12.75 ± 0.84 mol·L -1 after 72 h treatment, 24.82 ± 0.94 mol·L -1 after 48 h, and 61.41 ± 1.08 mol·L -1 after 24 h. In the present investigation, geraniin revealed growth inhibitory activity against A549 cells, which was superior to shikonin after treatments of 72 and 48 h and showed a similar result to shikonin after 24 h (Fig. 1) (Wu et al 2013). …”
Section: Cytotoxicity Of Geraniin In Vitrosupporting
confidence: 65%
“…SHK is not toxic to normal cells (25), but exerts cytotoxic effects against various neoplastic cells, and has not been demonstrated to promote anticancer drug resistance (26). However, its effects against lung cancer remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Shikonin can inhibit proliferation and induce apoptosis of human HepG2 cells (Yingkun et al, 2010). As an anticancer agent, shikonin circumvents cancer drug resistance in different cell lines (K562, MCF-7, and MDR cell K562/Adr) (Han et al, 2007;Wu et al, 2013). The results of the present study showed that shikonin inhibited proliferation and induced apoptosis of R-HepG2 cells.…”
Section: Discussionmentioning
confidence: 48%